Trends and drivers of fertiliser consumption in the South African agricultural industry - Ottermann, H. T.; Truter, K. J.; Haarhoff, S. J.; van der Westhuizen, D.; Meyer, F.; Swanepoel, P. A. (Agrekon, 2025)
The South African fertiliser industry plays a crucial role in supporting agriculture and ensuring food security. However, the country's dependence on fertiliser imports and inefficiencies in the supply chain pose significant economic and environmental challenges. Although South African farmers have managed to improve fertiliser use efficiency over time, broader application of precision agriculture technologies can enhance fertiliser use efficiency in the future. Sustainable practices and informed policies are necessary to balance agricultural productivity with environmental protection. This study provides an overview of fertiliser import trends, key driving factors, and future perspectives on fertiliser sources and emerging technologies. The study highlights the importance of fertilisers in addressing nutrient deficiencies in key grain-producing regions, such as the Free State, North West, and Western Cape provinces. South Africa's reliance on imports exposes the sector to price volatility and disruptions in the supply chain, influenced by global events like geopolitical tensions and the COVID-19 pandemic. While stable suppliers of imported products like Saudi Arabia and emerging markets like Qatar offer opportunities, challenges remain, including high costs and environmental risks. Precision agriculture technologies offer promising solutions to optimise fertiliser use and mitigate environmental impacts. The article discusses how targeted strategies and the adoption of precision agriculture technologies, such as variable rate applications, can enhance fertiliser efficiency. It also explores the implications of global environmental regulations and alternative fertiliser sources. Ultimately, the study emphasises the need for targeted policies to ensure a sustainable fertiliser supply while meeting the evolving demands of South Africa's agricultural sector.